Analysis of The Influence of Supplier and Government Partnerships on Hospital Supply Chain Performance - Aiko Pasaribu; Roland Y. H. Silitonga; Marla Setiawati (Petra International Journal of Business Studies, 2024)
Indonesia's healthcare industry has expanded rapidly alongside population growth to 278 million by 2023, driving a notable increase in healthcare expenditure. Hospitals form the backbone of healthcare provision, Within the complex landscape of the healthcare industry, the hospital supply chain (HSC) is crucial for ensuring the timely delivery of medical resources. Partnerships may play a crucial role in improving an HSC’s overall performance. This study employs System Dynamics modeling to analyze the impact of supplier and government partnerships on HSC performance. The study extends the existing literature by incorporating both CLD and SFD methodologies to provide a more comprehensive analysis of the factors and intricacies within hospital supply chain partnerships. The findings indicate that high trust, IT integration, and hospital dynamic capabilities improve hospital supply chain performance through better information sharing and integration. Hospital demand significantly influences government regulations and control, further affecting performance. Theoretically, this study advances how dynamic interactions and feedback loops between multiple stakeholders within the HSC can be effectively modeled to gain insight and enhance healthcare supply chains.